Between Nesfatin-1 Level and Insulin Resistance in Gestational Diabetes (Indian Journal of Public Health Research & Development, 2020)
Background & Aims: Stroke is a significant health problem with high prevalence and mortality worldwide.In Indonesia, it is the first leading cause of death after ischemic heart disease in 2017. As Barthel Index hasbeen regarded as the best outcome measure used in rehabilitation of people with stroke, this study sought todetermine the construct validity of the Indonesian version of the tool. Specifically, the study looked into theinter-rater reliability of the tool, the problems encountered by participants with the English version and thecorresponding modifications to be incorporated in the Indonesian version.Method: Utilizing an exploratory sequential mixed method design and involving five different groups ofparticipants with a total of 391, the study began with the forward and backward translation of the EnglishBarthel Index followed by the validation, reliability and validity testing of the Indonesian version.Result: Results showed that inter-rater reliability is satisfactory. Some terms in the English version weremodified to suit the linguistic and cultural context of Indonesia. In terms of content validity, the Indonesianversion of Barthel Index is acceptable. The construct validity test revealed two major factors, namely,functional performance and physiological function.Conclusion: it thereby provides a baseline data to advance knowledge on the use standardized tool like BI,to further improve nursing practice in the stroke room, and to enhance the nursing education curriculum.
Keywords: Construct Validity, Barthel index, Post Stroke